Na3PO4 assistant dispersion of nano-CaCO3 template to enhance electrochemical interface: N/O/P co-doped porous carbon hybrids towards high-performance flexible supercapacitors. (15th October 2020) - Wen, Yanliang; Liu, Xiaoguang; Wen, Xin; Chen, Xuecheng; Szymańska, Karolina; Dobrzyńska, Renata; Mijowska, Ewa
Abstract: Recently porous carbon hybrids have attracted ever-increasing attention as electrode materials for supercapacitors, but it remains a great challenge to simultaneously control their pore structure and element composition with optimal electrochemical performances. Herein, Na3 PO4 assistant dispersion of nano-CaCO3 template in egg white was proposed to fabricate nitrogen/oxygen/phosphorus (N/O/P) co-doped 3D hierarchical porous carbon hybrids. The as-prepared carbon exhibited a high surface area (2576 m 2  g −1 ), well-balanced pore size distribution with a large micropore volume (0.77 cm 3  g −1 ) and multi-heteroatoms doped carbon skeleton (3.9% of N, 12.2% of O and 4.1% of P). These physicochemical advantages were synergistically beneficial to supercapacitive performances: an ultrahigh capacitance of 452 F g −1 at 0.5 A g −1 in 6 M KOH electrolyte and excellent stability of 92.4% capacitance retention after 10000 cycles at 10 A g −1 . The energy density was 22.6 Wh kg −1 at the power density of 225.0 W kg −1 in the neutral electrolyte of 1 M Li2 SO4 . Especially, a flexible symmetric solid-state supercapacitor was assembled, which delivered a high capacitance (166 F g −1 ) and excellent flexibility (86.3% capacitance retention) with bending angles to 180°. Thus, this work provides a cost-effective strategy to fabricate multi-element co-doped 3D hierarchical porous carbon and expand its application for flexible energy storage devices. Graphical abstract: Image 1 Highlights: Na3 PO4 assistant dispersion of nano-CaCO3 template. N/O/P co-doped 3D hierarchical porous carbon from egg white. The carbon-based electrode displayed ultrahigh capacitance of 452 F g −1 . It delivered excellent flexibility of 86.3% capacitance retention with bending to 180°.